2006
DOI: 10.1128/aem.72.2.1135-1140.2006
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of the Food-Borne Pathogens Listeria monocytogenes and Salmonella enterica Serovar Poona on Fresh-Cut Apples with Naturally Occurring Bacterial and Yeast Antagonists

Abstract: Fresh-cut apples contaminated with either Listeria monocytogenes or Salmonella enterica serovar Poona, using strains implicated in outbreaks, were treated with one of 17 antagonists originally selected for their ability to inhibit fungal postharvest decay on fruit. While most of the antagonists increased the growth of the food-borne pathogens, four of them, including Gluconobacter asaii (T1-D1), a Candida sp. (T4-E4), Discosphaerina fagi (ST1-C9), and Metschnikowia pulcherrima (T1-E2), proved effective in prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 48 publications
3
65
0
5
Order By: Relevance
“…mL nalidixic acid (Nal) (Sigma Aldrich, St. Louis, MO, USA) through a combination of spontaneous mutation and repeated culture methods, in order to distinguish it from the background microflora indigenous to spinach leaves. Similar to the previous reports by other researchers (Leverentz et al, 2003(Leverentz et al, , 2006, L. monocytogenes was found to be resistant to 250 mg/mL Nal. L. monocytogenes grown overnight in TSB supplemented with 250 mg/mL Nal (TSBN250) reached 8 log CFU/mL.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…mL nalidixic acid (Nal) (Sigma Aldrich, St. Louis, MO, USA) through a combination of spontaneous mutation and repeated culture methods, in order to distinguish it from the background microflora indigenous to spinach leaves. Similar to the previous reports by other researchers (Leverentz et al, 2003(Leverentz et al, , 2006, L. monocytogenes was found to be resistant to 250 mg/mL Nal. L. monocytogenes grown overnight in TSB supplemented with 250 mg/mL Nal (TSBN250) reached 8 log CFU/mL.…”
Section: Resultssupporting
confidence: 81%
“…On average, throughout the course of the study, Lm-Nal R populations on spinach pieces stored under MA and AA were roughly equivalent. The observed reductions in Lm-Nal R populations on fresh-cut spinach treated with ListShield TM are in agreement with results of previous studies (Leverentz et al, 2004(Leverentz et al, , 2006. Supporting the results of this experiment, a recent study concluded that the same MA conditions used in this study in combination with an Escherichia coli O157:H7-specific lytic phage mixture resulted in lower E. coli O157:H7 populations on fresh-cut leafy greens compared to populations on phage-treated, inoculated samples packaged with atmospheric air (Boyacioglu et al, 2013).…”
Section: Disclosure Of Potential Conflicts Of Interestsupporting
confidence: 82%
“…Outbreaks caused by L. monocytogenes have been associated with ingestion of a variety of contaminated foods and were reported from many countries, including Australia, Switzerland, France, and the United States [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the use of several chemical substances, different bio preservatives are used to prevent the microbial spoilage of minimally processed vegetables. (Haye et al, 2008;Allende et al, 2007;Brown et al, 2011;Leverentz et al, 2006). Minimally processed vegetables are susceptible to microbial growth because they are cut parts of vegetables.…”
Section: Susceptibility To Microbiological Spoilagementioning
confidence: 99%